IISR Avinash – a rhizome rot resistant and high yielding variety of cardamom (Elettaria cardamomum Maton) - Ravindra Mulge, M N Venugopal, D Prasath, (Journal of Spices and Aromatic Crops, 2006)
The cardamom (Elettaria cardamomum) variety, IISR Avinash (RR-1) was developed at theIndian Institute of Spices Research, Cardamom Research Centre, Appangala (Karnataka),through clonal selection and recommended for release for its resistance to rhizome rot dis-ease and high yield. The average yield of IISR Avinash was 643 kg ha-1 (dry) with a poten-tial yield of 979 kg ha-1 (dry) with good quality dark green capsules.